Small Modular Reactors (SMRs) as a Solution for Renewable Energy Gaps: Spatial Analysis for Polish Strategy - Zarębski, Patrycjusz; Katarzyński, Dominik (Energies (Basel), 2023)
The integration of Small Modular Reactors (SMRs) into energy systems requires a meticulous assessment of various factors, spanning renewable energy potential, legal frameworks, technical considerations, community engagement, and consumer preferences. This article synthesizes a multifaceted discussion on the subject, focusing on the need for comprehensive analyses before deciding to implement SMRs. Drawing insights from geographic information systems (GIS) and lessons from renewable energy development in Poland, this paper underscores the significance of aligning energy strategies with local needs, emphasizing stakeholder participation. This study examines the factors influencing location attractiveness for various energy technologies, including small modular nuclear reactors (SMRs), wind, solar, and hydroelectric power plants, within Poland. Employing 17 indicators sourced from Statistics Poland and URE, coupled with the application of the k-means algorithm, we outline four distinct clusters that delineate the zones of location attractiveness for SMRs and other renewable energy sources. While large and medium-sized cities exhibit optimal location attractiveness, coastal counties in northern Poland emerge as more suitable for renewable energy sources than for SMRs. The study outlines four distinct energy development strategies based on typologies of regions, each tailored to maximize the utility of available resources and minimize environmental impact. The strategies encompass renewable energy utilization, energy efficiency enhancement, energy diversification, and adaptation through innovation. Emphasizing the interplay between renewable energy potential, energy demand, and local conditions, the research suggests the strategic deployment of SMRs as part of an energy mix in areas where renewable energy resources are limited. By leveraging SMRs’ continuous energy production, these reactors can complement intermittent renewables, bolstering energy security.